Práxis de educação ambiental: o caso de uma escola em área de palafitas, no município de Afuá, Pará - Brasil - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
The practice of environmental education (EE) at school is fundamental nowadays, for the construction of a school community that is fairer and more aware of issues related to problems triggered in the environment, and also have a perception of the importance of its performance in this environment; being able to carry out a contextualized reading in the global, regional scope and with its daily reality, in the high formation of critical participants. The main objective of the study was to analyze the practice of EE in a school in the municipality of Afuá (PA). For the development of the research, the qualitative/quantitative approach was based on the methodology, with the inductive method. The data for analysis were collected through official documents and online subjective forms applied to 04 technicians from SEMED/Afuá, 03 representatives of the technical school manager, vice-principal, pedagogical coordinator and 08 elementary school teachers from a school in the municipality of Afuá, located in the Marajó Region, state of Pará. The results of the research were: the critical systematization of public policy instruments at Federal, State and Municipal levels that subsidize EE praxis at school; the school's pedagogical practices reveal that EE primarily focuses on socio-environmental and cultural aspects of the reality in which it is inserted “area of stilt houses”; the interdisciplinary EE activities occur associated with the dates alluding to the day of the environment, among others. It is important for SEMED/Afuá-PA to implement EE with greater intensity, linked to the interdisciplinary process in Elementary Schools in the urban area, encouraged through actions/projects and/or recreational educational activities correlated with environmental themes and their development for improvement of the environment.
Keywords: Educação Ambiental; Práxis Educativa; Políticas Públicas; Escola em Palafitas; Políticas Públicas, Diversidade e Desenvolvimento Amazônico